Beyond the 150 min target: rethinking exercise promotion for active health in community-dwelling older adults through inclusive social prescribing - Kang, Ning; Chengmeng Zhang; Mei, Donghui; Huang, Qiongyu; Wang, Dongmin (Frontiers in Public Health, 2026)
Physical activity guidelines commonly recommend that older adults engage in at least 150–300 min of moderate intensity aerobic activity each week, combined with muscle strengthening and balance training. Although this target is clear, measurable, and useful for public health monitoring, it may be insufficient when directly applied to community-dwelling older adults who are frail, multimorbid, socially isolated, digitally excluded, or constrained by unsafe environments and limited care resources. For these populations, the central challenge is not only whether they can meet a weekly exercise volume, but whether they can preserve the functional abilities needed for independent living, social participation, and active aging. This Perspective argues for moving exercise promotion for community-dwelling older adults beyond a narrow adherence-based view of the 150-min target and toward a function-oriented paradigm of active health. We propose an integrated framework that places functional preservation at the center, uses micro dose exercise as an accessible entry point, applies Behavior Change Techniques to translate recommendations into sustainable daily habits, embeds exercise within community life through social prescribing, and supports long-term participation through human and digital collaboration. This approach does not reject existing physical activity guidelines. Rather, it reframes them as flexible references that can be adapted to older adults’ heterogeneous bodily conditions, social contexts, and everyday routines. By shifting from exercise adherence to long-term functional integration, community-based exercise promotion can become more inclusive, equitable, and feasible for older adults who are most likely to be left behind by standard dose-based models.